The International Monetary Fund’s Role in Overcoming Economic Crisis in PIIGS - Kinga Jasiak (Polish Political Science Yearbook, 2019)
The financial crisis started in 2008 and touched the whole world but some countries experienced its consequences more than others. The European Union and in particular eurozone, slid into a stage of economic recession. Five of 28 EU countries faced the edge of financial fall, named PIIGS-Portugal, Italy, Ireland, Greece and Spain. Multidimensionality of the global crisis have caused that international economic organizations faced a great challenge, For them it was a test of efficiency and effectiveness. The leading role in this period belonged to the International Monetary Fund (IMF), which is standing on the guard of the whole international currency system. The aim of the article is to draw and analyze the most important IMF activities towards PIIGS, especially what instruments were proposed as a help and what changes had to be made by receiving states in order to receive the financial support. The ten-year perspective taken in the article allows for the more comprehensive assessment of the issue.